Analysis of Pharmacy Service Performance Improvement for BPJS Patients Using The Lean Method at XYZ Hospital - Nur, Rahmi M; Zai, Yovita Yulia M.; Iskandar, Habibillah (Journal of Engineering Science and Technology Management (JES-TM), 2025)
Pharmacy services are a critical support unit within the healthcare system of hospitals, particularly for BPJS (Indonesia's National Health Insurance) patients, whose numbers continue to rise. However, pharmacy service processes often face several challenges, including prolonged waiting times, inefficient queues, lengthy initial registration procedures, and drug stock mismatches. This study aims to analyze and propose performance improvements in pharmacy services for BPJS patients at XYZ hospital using a Lean approach. The method employed in this research is Value Stream Mapping (VSM) to map out the service flow and identify waste. Data were collected through direct observation, interviews, and documentation, covering initial process mapping, service time for each process activity, and the number of prescriptions served monthly. The analysis revealed several non-value-adding activities affecting service efficiency, such as high waiting times, inefficient staff movements, drug stockouts, and disorganized drug storage. After implementing improvements based on Lean principles, average patient waiting time decreased, with compounding drug service time reduced from 23 to 20 minutes and non-compounded drug service time reduced from 17 to 14 minutes. The study concludes that applying the Lean method can significantly enhance the performance of pharmacy services. Strategic recommendations are also provided to maintain work efficiency and ensure continuous quality improvement at XYZ Hospital.